2022
DOI: 10.1038/s41467-022-33496-2
|View full text |Cite
|
Sign up to set email alerts
|

Continuously processing waste lignin into high-value carbon nanotube fibers

Abstract: High value utilization of renewable biomass materials is of great significance to the sustainable development of human beings. For example, because biomass contains large amounts of carbon, they are ideal candidates for the preparation of carbon nanotube fibers. However, continuous preparation of such fibers using biomass as carbon source remains a huge challenge due to the complex chemical structure of the precursors. Here, we realize continuous preparation of high-performance carbon nanotube fibers from lign… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
52
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 84 publications
(76 reference statements)
0
52
0
Order By: Relevance
“…It provides an expandable idea for manufacturing highly conductive fibers with excellent mechanical properties. Liu et al 112 achieved the synthesis of high-performance CNT fibers from lignin through a systematic integration of solvent dispersion, high thermal degradation, catalytic synthesis and assembly (Fig. 14d).…”
Section: Manufacturing Methodsmentioning
confidence: 99%
“…It provides an expandable idea for manufacturing highly conductive fibers with excellent mechanical properties. Liu et al 112 achieved the synthesis of high-performance CNT fibers from lignin through a systematic integration of solvent dispersion, high thermal degradation, catalytic synthesis and assembly (Fig. 14d).…”
Section: Manufacturing Methodsmentioning
confidence: 99%
“…[165] Liu et al reported the continuous fabrication of CNT fibers from waste lignin by solvent dispersion, high-temperature pyrolysis, catalytic reaction, and assembly. [166] The production process is illustrated in Figure 5e. The production rate of ligninderived CNT fiber is up to 120 m h −1 and CNT fiber possesses a high tensile strength of 1.33 GPa as well as an electrical conductivity of 1.19 × 10 5 S m −1 .…”
Section: D Structurementioning
confidence: 99%
“…e) Synthesis mechanism from lignin to CNT fibers and its respective processing schematic. Reproduced with permission [166]. Copyright 2022, The authors, Springer Nature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Biomass resources are recently considered as an alternative to petroleum‐based resources and attract widespread attention in the development of sustainable energy sources [1, 2] . As a naturally abundant polymeric material extracted from biomass, [3–7] lignin contains a large number of aromatic ring structures that can be used as precursors for preparing carbon and graphitic materials [8, 9] . However, lignin technology has not been fully developed to date [10, 11] .…”
Section: Introductionmentioning
confidence: 99%